Understanding of Medication Information in Primary Health Care: A Cross-Sectional Study in a South Eastern European Population - Roshi, Dajana; Burazeri, Genc; Schröder-Bäck, Peter; Toçi, Ervin; Italia, Salvatore; Ylli, Alban; Brand, Helmut (Frontiers in Public Health, 2020)
Aim: We aimed to assess the level of information about use and administration of medications prescribed by family physicians to adult primary health care (PHC) users in a transitional South Eastern European population.We aimed to assess adult primary health care (PHC) users’ understanding of their medication information in a transitional South Eastern European population across seven domains. Methods: A cross-sectional study, carried out in Albania in 2018-19, included a representative sample of 1553 PHC users aged ≥18 years (55%women; overall mean age: 54.6±16.4 years; overall response rate: 94%). Participants were asked about their understanding of information they received from their respective family physicians about prescribed medicines in terms of factors like cost, dosage, and side-effects.Participants were inquired about the information received by their respective family physicians in cases when they were prescribed medicines. Socio-demographic data were also gathered. Binary logistic regression was employed to assess the socio-demographic predictors of information about medication use and administration. Results: Across different aspects of use and administration, 21%-60% of participants did not understand their medications.Overall, 21%-60% of participants usually did not understand different aspects related to the information about use of medications prescribed by their family physicians. Less understanding of medication use was particularly high among the poor and those with low education and among urban residents, irrespective of socioeconomic status.The lack of understating of the information about medication use was particularly higher among the poor and the low educated individuals and, irrespective of the socioeconomic status, among urban residents. Conclusion: This study provides important evidence on about the level and socio-demographic determinants of on understanding of the information about medication use and administration among adult PHC users in a transitional former communist country in South Eastern Europe. Policymakers should be aware of the joint role and interplay between health literacy (demand side) and information provision (supply side), which both significantly influence the understanding of medication use by the general population.